The effects of novokinin, an AT2 agonist, on blood pressure, vascular responses, and levels of ADMA, NADPH oxidase, and Rho kinase in hypertension induced by NOS inhibition and salt - Mutlu, Emre; Ilhan, Selcuk; Onat, Elif; Kara, Murat; Sahna, Engin (Tubitak Scientific & Technological Research Council Turkey, 2016)
Background/aim: The effects of AT 2 receptor agonist novokinin on blood pressure, eNOS, NADPH oxidase, protein arginine methyltransferases (PRMTs), and Rho kinase in hypertension were investigated. Furthermore, in isolated thoracic aorta rings, contractile and dilator responses were studied. Materials and methods: To develop hypertension, L-NAME was administered intraperitoneally and salt was given with tap water (1%) for 4 weeks. Novokinin was administered intraperitoneally for the last 2 weeks. Blood pressures were measured using the tail-cuff method and enzyme levels by real-time polymerase chain reaction in aortic tissues. Results: Blood pressure increased significantly in hypertensive rats. Novokinin reduced the blood pressure in the hypertensive group. While the contractile responses to increasing doses of angiotensin II were increased, vascular reactivity (Emax) and sensitivity (EC50) to acetylcholine were decreased in hypertensive rats. In novokinin-treated hypertensive groups, the EC50 value decreased and the Emax value for acetylcholine significantly increased. The levels of Rho kinase and PRMT expression increased and the level of eNOS expression decreased in the hypertensive group. In novokinin-treated rats, ADMA, NADPH oxidase, and Rho kinase tended to decreased, but these changes did not reach statistical significance. Conclusion: Although further studies are needed to determine its effectiveness, the AT2 agonist novokinin may be a novel agent that is promising in terms of protective effects for the treatment of hypertension.
Keywords: ADMA; AT2 receptor; hypertension; nitric oxide; novokinin; Rho kinase